Diferentes experiências vividas a partir da percepção ambiental: o livro de registro e o parque - Marcos Clair Bovo (Terr@ Plural)
his paper discusses theoretical considerations based on Humanistic Geography, establishing a relationship between space and place. Thus, the research aims to identify and characterize users’ perceptions of Vila Rica do Espírito Santo State Park, based on Fênix, Paraná state, considering people’s impressions documented in the park’s register book memorial, written between 1990 and 1997. To do that, the following question was raised: “How can we understand the park as a place, space, and landscape given the visitors’ images and feelings?” To answer that, we established four categories: the beauty and richness of the park; the poetic; the archaeology museum; and the transcription and interpretation of passages from the logbook, considering different perceptions regarding the park. The results suggest the presence of affective, ecological, and historical values that are perceived and experienced by the visitors.